2021
DOI: 10.1001/jamanetworkopen.2021.0945
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Cancer Prevalence in Patients With Neurofibromatosis Type 1 at an Academic Cancer Center vs in the General Population From 1985 to 2020

Abstract: IMPORTANCE Neurofibromatosis type 1 (NF1) is a complex genetic disorder that is associated with not only neurofibromas, but also an increased susceptibility to other neoplasms. OBJECTIVE To evaluate the prevalence of neoplasia and outcomes among patients with NF1. DESIGN, SETTING, AND PARTICIPANTS This cohort study was conducted among patients with NF1 at a single academic cancer center from 1985 to 2020 with median (range) follow-up of 2.9 years (36 days to 30.5 years). Of 2427 patients evaluated for NF1, 160… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
84
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(97 citation statements)
references
References 53 publications
5
84
0
8
Order By: Relevance
“…It has been shown that NF1 patients have decreased life expectancy of 15 years compared to the general population [ 12 ]. Malignant tumors and vascular disease have been significantly associated with the death of NF1 patients aged <40 years [ 13 ].…”
Section: Neurofibromatosis Typementioning
confidence: 99%
“…It has been shown that NF1 patients have decreased life expectancy of 15 years compared to the general population [ 12 ]. Malignant tumors and vascular disease have been significantly associated with the death of NF1 patients aged <40 years [ 13 ].…”
Section: Neurofibromatosis Typementioning
confidence: 99%
“…El 50% de los pacientes llega a sufrir metástasis a los 5 años del diagnóstico primario, principalmente en el hígado, por lo que es fundamental su detección y tratamiento oportuno. En casos como el actual, por el antecedente de neurofibromatosis, se presentan tasas más altas de neoplasias, asociadas a disminución de la esperanza de vida [2]. La radioterapia es el tratamiento local más apropiado para pacientes con neoplasias de pequeño tamaño, que no presentan afectación extraocular, con el objetivo de preservar el globo ocular.…”
Section: Discussionunclassified
“…La edad media de afectación es de 62 años [1]. La neurofibromatosis es un trastorno autosómico dominante, dicha afectación se asocia al desarrollo más temprano y frecuente de neoplasias, dentro de las que se puede mencionar el melanoma, quienes presentan una esperanza de vida de hasta 15 años menos que la población en general [2]. Se presenta el caso de un paciente masculino de 55 años de edad con con melanoma uveal y antecedente de neurofibromatosis.…”
Section: Introductionunclassified
“…50% of neurofibromatosis type 1 cases are hereditary, the rest of them are due to de novo NF1 mutations. Neurofibromatosis type 1 is a multisystem disease and patients are at high risk of cancer [3,4]. The life span of individuals with NF1 is generally short and mortality is higher in younger individuals (<40 years) compared to the general population.…”
Section: Introducti̇onmentioning
confidence: 99%